1999
DOI: 10.1021/ja990456k
|View full text |Cite
|
Sign up to set email alerts
|

Alkylation of Nucleic Acids by a Model Quinone Methide

Abstract: Quinone methides and related electrophiles represent a common class of intermediates that form during metabolism of drugs and xenobiotics and may lead to DNA alkylation. The intrinsic reactivity of these species has now been characterized using a stable model compound, O-(tert-butyldimethylsilyl)-2-bromomethylphenol, designed to generate an o-quinone methide in the presence of fluoride. The resulting deoxynucleoside adducts were assigned unambiguously through use of two-dimensional NMR and, in particular, hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
229
2
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 141 publications
(245 citation statements)
references
References 59 publications
12
229
2
2
Order By: Relevance
“…The potential barriers for migration of bisQM2 across DNA were pushed beyond a canonical or nicked duplex to include an analogue containing a bulge structure formed by two extrahelical Ts. Ts were chosen for their lack of reaction with the parent QM 61 and inserted into the sequence of OD6 resulting in a new strand OD7. This new strand was then used to displace OD4 from its crosslinked duplex with OD2.…”
Section: Resultsmentioning
confidence: 99%
“…The potential barriers for migration of bisQM2 across DNA were pushed beyond a canonical or nicked duplex to include an analogue containing a bulge structure formed by two extrahelical Ts. Ts were chosen for their lack of reaction with the parent QM 61 and inserted into the sequence of OD6 resulting in a new strand OD7. This new strand was then used to displace OD4 from its crosslinked duplex with OD2.…”
Section: Resultsmentioning
confidence: 99%
“…Pande and colleagues have developed an experimental model to study the reactivity of o-QMs (2) generated in situ in the presence of synthetic DNA [86]. They have shown that, just as other alkylating agents, such as cisplatin, this particular QM binds with a great selectivity to particular bases.…”
Section: Modulation Of Qm Reactivity Towards Nuc-leophiles Drugs Withmentioning
confidence: 99%
“…11) (along with more recent duocarmycin derivatives) is among the most potent antitumor agents discovered to date [86][87][88][89][90][91]. Strictly speaking, CC-1065 is not a QM, but the cyclopropane moiety present on its structure is, from a reactivity point of view, a bioisosteric form of the methide found in QMs.…”
Section: Modulation Of Qm Reactivity Towards Nuc-leophiles Drugs Withmentioning
confidence: 99%
“…22 Initial model studies suggested a selectivity of QM for weak nucleophiles and an ability of some adducts to form reversibly. 19,[23][24][25][26] Further investigation revealed that this unusual selectivity was a function of QM adduct stability rather than initial product formation. [27][28][29] In contrast to earlier assumptions, the strongest nucleophiles of DNA reacted most quickly with a simple ortho-QM model to form kinetic products.…”
Section: Introductionmentioning
confidence: 99%